Keanekaragaman Pohon dan Leaf Area Index (LAI) di Tahura Pancoran Mas Kota Depok, Jawa Barat - Rizal Yoga Saputra; Sri Setiawati Tumuyu; Siti Badriyah Rushayati (Universitas PGRI Silampari, 2026)
Tahura Pancoran Mas, located in Depok City, West Java Province, is Indonesia's first nature reserve and constitutes a critical area for ecological research. Despite its significant ecological role, detailed data on tree diversity and Leaf Area Index (LAI), which represents canopy density, have not been systematically recorded across its management zones, namely the Protection Zone, Utilization Zone, and Collection Zone. This study aimed to analyze tree diversity and canopy density (LAI) across these three zones. Tree diversity data were collected using a modified transect line method consisting of nine plots, each measuring 20 × 20 meters. Canopy structure was recorded using digital hemispherical photography, tree species diversity was measured using the Shannon-Wiener index (H'), and LAI values were processed using the Hemiview software. A total of 81 individual trees were recorded, representing 20 species belonging to 13 families. Dominant species were identified in each zone: Artocarpus elasticus Reinw. ex Blume in the Protection Zone, Arenga pinnata (Wurmb) Merr. in the Utilization Zone, and Sandoricum koetjape (Burm.f.) Merr. in the Collection Zone. Biodiversity evaluation revealed that the mean Shannon-Wiener index across all three zones fell within the moderate category (Protection Zone H' = 2.20; Utilization Zone H' = 1.75; Collection Zone H' = 2.35). LAI results indicated that canopy density was classified as very dense, with values of 2.89, 2.92, and 2.84 in the protection, utilization, and collection zones, respectively. These findings may serve as a scientific reference for developing sustainable management strategies for the Tahura Pancoran Mas area, including planting native tree species appropriate to the ecological conditions of the Utilization Zone, environmental education programs, and periodic vegetation monitoring.